Efficient export of prefolded, disulfide‐bonded recombinant proteins to the periplasm by the Tat pathway in Escherichia coli CyDisCo strains. (22nd January 2014) - Matos, Cristina F. R. O.; Robinson, Colin; Alanen, Heli I.; Prus, Piotr; Uchida, Yuko; Ruddock, Lloyd W.; Freedman, Robert B.; Keshavarz‐Moore, Eli
<x xml:space="preserve">Abstract</x> Numerous high‐value therapeutic proteins are produced in Escherichia coli and exported to the periplasm, as this approach simplifies downstream processing and enables disulfide bond formation. Most recombinant proteins are exported by the Sec pathway, which transports substrates across the plasma membrane in an unfolded state. The Tat system also exports proteins to the periplasm, but transports them in a folded state. This system has attracted interest because of its tendency to transport correctly folded proteins, but this trait renders it unable to export proteins containing disulfide bonds since these are normally acquired only in the periplasm; reduced substrates tend to be recognized as incorrectly folded and rejected. In this study we have used a series of novel strains (termed CyDisCo) which oxidise disulfide bonds in the cytoplasm, and we show that these cells efficiently export a range of disulfide‐containing proteins when a Tat signal peptide is attached. These test proteins include alkaline phosphatase (PhoA), a phytase containing four disulfide bonds (AppA), an antiinterleukin 1β scFv and human growth hormone. No export of PhoA or AppA is observed in wild‐type cells lacking the CyDisCo factors. The PhoA, AppA and scFv proteins were exported in an active form by Tat in the CyDisCo strain, and mass spectrometry showed that the vast majority of the scFv protein was disulfide‐bonded and correctly processed. The evidence indicates that this combination of Tat + CyDisCo offers a novel means of exporting active, correctly folded disulfide bonded proteins to the periplasm. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:281–290, 2014